C1ql4 regulates breast cancer cell stemness and epithelial-mesenchymal transition through PI3K/AKT/NF-κB signaling pathway - Xu, Fan; Wang, Jiali; Zhen, Shuman; Duan, Yuqing; Li, Qingshan; Liu, Lihua (Frontiers in Oncology, 2023)
Background: The stemness characteristic of breast cancer (BC) is a crucial factor underlying cancer recurrence and metastasis after operative therapy and chemoradiotherapy. Understanding the potential mechanism of breast cancer stem cells (BCSCs) may ameliorate the prognosis of patients. Methods: We collected clinical specimens of BC patients for staining and statistical analysis to verify the expression status and clinical significance of C1ql4. Western blot and qRT-PCR were emplyed to detect the expression of molecules. Flow cytometry was used to examine cell cycle, cell apoptosis and the portion of BCSCs. Wound healing and Transwell assays were used to demonstrate cell metastasis. The effect of C1ql4 on breast cancer progression in vivo was examined in a nude mouse tumor bearing model. Results: Our clinical analysis has shown that C1ql4 was highly expressed in BC tissues and cell lines, and its overexpression was significantly related to the malignancy of BC patients. Moreover, we also found that C1ql4 was overexpressed in BCSCs. C1ql4 knockdown suppressed the BCSC and EMT properties, promoted cell cycle progression, enhanced BC cell apoptosis, and inhibited cell migration and invasion, whereas the C1ql4 overexpression exhibited the opposite effects. Mechanistically, C1ql4 promoted the activation and nuclear location of NF-κB and the expression of downstream factors TNF-α and IL-1β. Moreover, inhibition of PI3K/AKT signaling suppressed the C1ql4-induced stemness and EMT. Conclusions: To summarize, our findings suggest that C1ql4 promotes the BC cell stemness and EMT via modulating the PI3K/AKT/NF-κB signaling, and provides a promising target for BC treatment.